Dampak Regulasi Penanaman Modal Asing dalam Sektor Logistik terhadap Daya Saing Nasional - Aprillidayanti, Aprillidayanti (Universitas Batanghari Jambi, 2025)
Foreign investment (FDI) is one of various ways to encourage economic growth and country development. The logistics sector as one of the supporting sectors in development plans plays an important role in supporting the efficient distribution of goods and services throughout the archipelago. Business activities, including those containing foreign capital, require conducive legal regulations to create legal certainty, which is an important indicator of political and economic stability. This research aims to examine the impact of foreign investment regulations in the logistics sector on national competitiveness in order to provide legal certainty to all business actors, both domestic and foreign, and prosperity for all Indonesian people using normative juridical research methods or using existing laws and regulations. At the moment. The results of the research show that the government has created foreign investment regulations related to the logistics sector in quite detail, but in its implementation it must refer to various relevant laws and regulations and there is no difference in treatment between logistics business activities from domestic and foreign investors.